Chemical and Organoleptic Characteristics of Pempek Using Different Ratios of Lampam Fish Surimi and Tapioca Flour - Dasir Dasir; Suyatno Suyatno; Putri Anisa Amnes (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The use of lampam fish as a raw material for pempek is a new effort to overcome the high cost of snakehead fish. The study aims to determine the chemical and organoleptic characteristics of pempek using a comparison of lampam fish surimi with tapioca flour. The study was conducted in the laboratory of the Muhammadiyah University of Palembang and the Agricultural Product Technology laboratory, Faculty of Agriculture, Sriwijaya University from December 2023 to February 2024. The study used a non-factorial randomized block design with five treatment levels, namely P1 (surimi 250 g:tapioca flour 350 g), P2 (surimi 300 g:tapioca flour 350 g), P3 (surimi 350:tapioca flour 350 g), P4 (surimi 400 g:tapioca flour 350 g), P5 (surimi 450 g:tapioca flour 350 g) with three replications. The research parameters include analysis of protein content and water content, organoleptic tests of color, aroma, taste, and elasticity. The results showed the highest protein content in P5 at 23.37% ± 0.10, and the highest water content in P5 at 59.11% ± 0.35. The highest level of preference for color was 4.28 ± 1.06 (like), aroma was 3.76±1.54 (rather like), taste was 3.84 ± 0.72 (rather like) and elasticity was 3.92± 1.00 (rather like) in P5.